The African Union policy environment toward enabling action for nutrition in Africa - Lokosang, Laila; Osei, Akoto; Covic, Namukolo (International Food Policy Research Institute, 2016)
The current AU policy environment supports efforts by African countries to address malnutrition and can be a rallying point for different interventions at the continental, REC, and country levels. In addition, the accountability processes incorporated into the various declarations create opportunities for monitoring nutrition progress across the continent. The chapters in this report reflect on the current status of nutrition in Africa and offer insight into some of the different approaches being used to improve nutrition outcomes as part of agriculture interventions. The ATOR also always includes a chapter (Chapter 12) that reports current progress on CAADP indicators.